The vascular properties of the BOLD signal - Driver, Ian D. (2012)
The work presented in this thesis is intended to contribute towards the understanding of the cerebral vascular behaviour in response to changes in neuronal activation. The blood oxygenation-level dependent (BOLD) functional magnetic resonance imaging (fMRI) signal provides an indirect measure of neuronal activation, arising from a combination of metabolic and vascular (blood flow and blood volume) changes local to the activation. Therefore the BOLD signal is dependent on local vascular properties as well as on the neuronal activation, leading to a variability of the BOLD signal, based on the underlying vascular structure. It has become an important goal to improve understanding of the mechanisms underlying the BOLD signal in order to separate out this vascular variability from the underlying correspondence with the neuronal activation.